Kepemimpinan Abdurrahman Ad – Dakhil dalam Mengibarkan Bendera Dinasti Umawiyah di Andalusia - Mainur Andriya; Umi Iriani; Ellya Roza (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This article aims to discuss the struggle of a descendant of the Umayyads who managed to escape the pursuit of the Abbasid army from the city of Damascus to Andalusia. He succeeded in re-establishing Umayyad rule in Andalusia after the collapse of their power in Damascus. Abdurrahman ad-Dakhil's leadership in Andalusia was an important turning point in Islamic history, which not only marked the continuation of the Umayyad legacy but also created a pluralist and progressive society. The research method was conducted by Library Research with a qualitative approach, the data was analysed using a qualitative descriptive approach and content analysis. The results showed that Abdurrahman Ad-Dakhil had a strong influence so that Islamic Spain could unite under his rule. He was very instrumental in building the government in Andalusia in such a way that the Andalusian State could compete with the influence of the Abbasid Daulah power in Baghdad. As such, he is one of the most important figures in Islamic history. He became an inspirational figure because of his persistence, his intelligence, his struggle in the enforcement of Islamic law. By analysing the policies and strategies he implemented, it reveals the significant impact on the development of culture, science, and art in Andalusia.